Updates on the coronavirus disease 2019 vaccine and consideration in children - Hyun Mi Kang; Eun Hwa Choi; Yae-Jean Kim (The Korean Pediatric Society, 2021)
Humanity has been suffering from the global severe acute respiratory syndrome coronavirus 2 pandemic that began late in 2019. In 2020, for the first time in history, new vaccine platforms-including mRNA vaccines and viral vector-based DNA vaccines-have been given emergency use authorization, leading to mass vaccinations. The purpose of this article is to review the currently most widely used coronavirus disease 2019 vaccines, investigate their immunogenicity and efficacy data, and analyze the vaccine safety profiles that have been published, to date.